Vessel Safety Monitoring System (VSMS) Based on LoRA for the Safety of Indonesian Traditional Fishers - Nofandi, Faris; Mahendra , R; Purwanti, Endang Pudji (Indonesian Journal of Engineering Research, 2022)
Based on data obtained from Indonesian fisheries statistics, over ten years, it is known that 90% of the fishing fleet in Indonesia is dominated by fishing vessels under 30 GT. Generally, these vessels are not equipped with the calculations of the shipping architect or planning drawings. the large percentage of shipping disasters or vessel accidents in Indonesia, including fishing vessel accidents, is caused by several factors: 43.67% due to human error, 32.37% due to nature, 23.94% due to technical factors. Accidents due to bad weather cannot be avoided during fishing operations. However, with the quality of human resources and technical factors that have improved, it is hoped that vessel accidents can be avoided or minimized. According to the Global Maritime Distress and Safety System (GMDSS), vessels with the IMO standard are already based on satellite communications. Vessels required to use the GMDSS standard are vessels with a size of 300 GT and above. We develop a Vessel Safety Monitoring System (VSMS) which has a lower cost, which can be used to determine the vessel’s position and is added by using a distress button system such as the satellite-based GMDSS system. the communication from the coast guard post to the vessel uses the LoRA module based on radio frequency, although without pressing the distress button on the vessel, the device on the vessel will continue to send location, vessel's speed, and rpm to the coast guard station. If the distress button is pressed, the location will still be sent, the buzzer at the coast guard post will turn on, and the vessel's location can be seen on the local web server so that the coast guard post officers can immediately find out the coordinates of the vessel. It can minimize the time to search for the vessel's location because the vessel's coordinates are known. Based on the results of the Vessel Safety Monitoring System (VSMS) test, 10 data transmission from the vessel to the coast guard post can work on the land and the sea it can send nine types of data with 0 - 50 meters distance, it can send 1 type of data with a 0 - 100 meters distance, with an average delivery delay of 5 seconds. The amount of data and the delivery delay affects the working distance of the tool. The distress function or the danger signal requires data transmission for 0-15 seconds manually or automatically until the alarm goes off at the coast guard post since the vessel's danger signal is activated from the vessel to the coast guard post